Chronology of key events of Riga Technical University - Zigmunde, Alīda; Lapsa, Rūta; Gudro, Ilze (History of Engineering Sciences and Institutions of Higher Education, 2018)
IN STUDY YEAR 2017/2018September 1Prime Minister of Latvia Māris Kučinskis attended the traditional meeting of RTU Rector with teaching staff and employees of RTU and presented to the Rector a Letter of Appreciation «For lifelong contribution to the development of Latvian science and persistent efforts to develop studies of exact sciences, innovation and technology transfer, thus enhancing the quality of education development of the national economy».